Self-diffusion in remodeling and growth - Epstein, M; Goriely, A (2012)
Self-diffusion, or the flux of mass of a single species within itself, is viewed as an independent phenomenon amenable to treatment by the introduction of an auxiliary field of diffusion velocities. The theory is shown to be heuristically derivable as a limiting case of that of an ordinary binary mixture. © 2011 Springer Basel AG.